Vitamin D modulates human macrophage response to Mycobacterium tuberculosis DNA. (May 2019) - Cervantes, Jorge L.; Oak, Esther; Garcia, John; Liu, Hongfei; Lorenzini, Paolo A.; Batra, Deepika; Chhabra, Arvind; Salazar, Juan C.; Roca, Xavier
Abstract: Mycobacterium tuberculosis (Mtb) is a facultative intracellular pathogen that infects macrophages where it avoids elimination by interfering with host defense mechanisms, including phago-lysosome fusion. Endosomal Toll-like receptors (TLRs) generate Type I Interferons (IFNs), which are associated with active tuberculosis (TB). We aimed to explore if DNA from different Mtb lineages lead to differences in the inflammatory response of human monocytic/macrophage cells. THP-1 cells which express two inducible reporter constructs for interferons (IFNs) as well as for NF-κB, were stimulated via endosomal delivery of Mtb DNA as a nanocomplex with PEI. DNA from different Mtb phylogenetic lineages elicited differential inflammatory responses in human macrophages. An initial relatively weak IRF-mediated response to DNA from HN878 and H37Rv increased if the cells were pre-treated with Vitamin D (Vit D) for 72 h. RNAseq of THP-1 under different transformation conditions showed that pre-treatment with Vit D upregulated several TLR9 variants, as well as genes involved in inflammatory immune response to infection, immune cell activation, Type I IFN regulation, and regulation of inflammation. Vit D appears to be important in increasing low IRF responses to DNA from certain lineages of Mtb. Variations in the IRF-mediated response to DNA derived from different Mtb genotypes are potentially important in the pathogenesis of tuberculosis since Type I IFN responses are associated with active disease. The role of Vit D in these responses could also translate into future therapeutic approaches.